The Influence of Social Media on the Effectiveness of Wardah Cosmetic Product Promotions - Maria, Vera; Safana, Nadzwa; Andrayani, Septi; Azahra, Septi (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This research aims to determine the effectiveness of Wardah product promotion through social media in increasing product sales. Social media makes it easy for a brand to promote and sell its products in a wide range, one of which is the local brand Wardah which is known as "halal cosmetics". From various social media, Wardah also utilizes e-commerce sites or known as online shops in selling its products. This research also discusses how Wardah is able to compete with other big brands. The method used in this research is a descriptive qualitative method. The author collects data by observing the object and conducting a literature study of previous research.